Elucidation of a potent pro-resolving mediator of inflammation resolution via human neutrophil–vascular endothelial cell interactions - Robert Nshimiyimana; Nan Chiang; Charles N. Serhan (Proceedings of the National Academy of Sciences, 2026)
The acute inflammatory response is a highly coordinated programmed sequence that enables neutrophils to transmigrate from venules into tissues. Ideally self-limited, the active resolution phase produces specialized molecules that stimulate resolution and prevent collateral tissue damage from excessive neutrophil infiltration. The superfamily of pro-resolving molecules is termed specialized pro-resolving mediators including the essential polyunsaturated fatty acid-derived lipoxins, resolvins, protectins, and maresins. Given the intimate interactions between leukocytes and endothelial cells in inflammation resolution, we investigated whether unique bioactive molecules carrying pro-resolution properties are biosynthesized by human neutrophils coincubated with activated vascular endothelial cells. Using metabololipidomics, we found that human coronary aortic valves from transplants contained 13-hydroxy-4Z,7Z,10Z,14E,16Z,19Z-docosahexaenoic acid (13-HDHA) and inflammatory eicosanoids. We report that human endothelial cells convert DHA to 13-HDHA which in turn is transformed by human neutrophils to a previously unknown bioactive product 4,13-dihydroxy-docosahexaenoic acid. This structure was established using physical properties including tandem-mass spectrometry, UV-analysis, and conversion of deuterated substrate. Biosynthesis of this product during neutrophil–endothelial coincubations involved bidirectional crosstalk between neutrophil 5-LOX and endothelial COX-2 as confirmed using isolated recombinant enzymes. The bioactive 4S,13R-dihydroxy-5E,7Z,10Z,14E,16Z,19Z-docosahexaenoic acid, also produced by M2-like macrophages and mononuclear cells, demonstrated potent nanomolar pro-resolving actions including, a) limiting neutrophil infiltration into mouse air pouch, b) reducing human neutrophil adherence to endothelial cells, c) protecting endothelial cell from senescence, and d) stimulating human macrophage efferocytosis of senescent red blood cells. These results provide evidence for a previously unknown pro-resolving pathway and molecule biosynthesized from DHA via cyclooxygenase-2–5-lipoxygenase during leukocyte crosstalk with the vasculature.